Prevalence and associated predictors for patients developing chronic neuropathic pain following burns. Issue 1 (1st May 2020) - Klifto, Kevin M; Dellon, A Lee; Hultman, C Scott
Abstract: Background: Chronic pain, unrelated to the burn itself, can manifest as a long-term complication in patients sustaining burn injuries. The purpose of this study was to determine the prevalence of chronic neuropathic pain (CNP) and compare burn characteristics between patients who developed CNP and patients without CNP who were treated at a burn center. Methods: A single-center, retrospective analysis of 1880 patients admitted to the adult burn center was performed from 1 January 2014 to 1 January 2019. Patients included were over the age of 15 years, sustained a burn injury and were admitted to the burn center. CNP was diagnosed clinically following burn injury. Patients were excluded from the definition of CNP if their pain was due to an underlying illness or medication. Comparisons between patients admitted to the burn center with no pain and patients admitted to the burn center who developed CNP were performed. Results: One hundred and thirteen of the 1880 burn patients developed CNP as a direct result of burn injury over 5 years with a prevalence of 6.01%. Patients who developed CNP were a significantly older median age (54 years vs. 46 years, p = 0.002), abused alcohol (29% vs. 8%, p < 0.001), abused substances (31% vs. 9%, p < 0.001), were current daily smokers (73% vs. 33%, p < 0.001), suffered more full-thickness burns (58% vs. 43%, p < 0.001), greater median percent of total body surface area (%TBSA) burns (6 vs. 3.5, p < 0.001), were more often intubated on mechanical ventilation (33% vs. 14%, p < 0.001), greater median number of surgeries (2 vs. 0, p < 0.001) and longer median hospital length of stay (LOS) (10 days vs. 3 days, p < 0.001), compared to those who did not develop CNP, respectively. Median patient follow-up was 27 months. Conclusions: The prevalence of CNP over 5 years was 6.01% in the burn center. Older ages, alcohol abuse, substance abuse, current daily smoking, greater percent of total body surface area (%TBSA) burns, third degree burns, being intubated on mechanical ventilation, having more surgeries and longer hospital LOS were associated with developing CNP following burn injury, compared to patients who did not develop CNP following burn injury.